A microcalorimetric approach for investigating stoichiometric constraints on the standard metabolic rate of a small invertebrate. (28th August 2018) - Ruiz, Thomas; Bec, Alexandre; Danger, Michael; Koussoroplis, Apostolos‐Manuel; Aguer, Jean‐Pierre; Morel, Jean‐Pierre; Morel‐Desrosiers, Nicole
Abstract: Understanding the determinants of metabolism is a core ecological topic since it permits to link individual energetic requirements to the ecology of communities and ecosystems. Yet, besides temperature, metabolic responses to environmental factors remain poorly understood. For example, it is commonly assumed that dietary stoichiometric constraints increase metabolism of small invertebrates despite scarce experimental support. Here, we used microcalorimetric measurements to determine the standard metabolic rate (SMR) of Daphnia magna fed stoichiometrically balanced (C/P: 166) or imbalanced (C/P: 1439). Daphnids fed imbalanced maintained their stoichiometric homeostasis within narrow boundaries. However, they consistently increased their SMR while decreasing their growth rate. Our measurements demonstrate that homeostatic regulation implies higher metabolic costs, thereby reducing available energy for growth. We demonstrate that microcalorimetry is a powerful and precise tool for measuring small‐sized organisms' metabolic rate, thus opening promising perspectives for understanding how environmental factors, such as nutritional constraints, affect organismal metabolism.